RNA helicase DEAD box protein 5 regulates Polycomb repressive complex 2/Hox transcript antisense intergenic RNA function in hepatitis B virus infection and hepatocarcinogenesis. Issue 4 (8th August 2016) - Zhang, Hao; Xing, Zheng; Mani, Saravana Kumar Kailasam; Bancel, Brigitte; Durantel, David; Zoulim, Fabien; Tran, Elizabeth J.; Merle, Philippe; Andrisani, Ourania
Abstract : Chronic hepatitis B virus (HBV) infection is a major factor in hepatocellular carcinoma (HCC) pathogenesis by a mechanism not yet understood. Elucidating mechanisms of HBV‐mediated hepatocarcinogenesis is needed to gain insights into classification and treatment of HCC. In HBV replicating cells, including virus‐associated HCCs, suppressor of zeste 12 homolog (SUZ12), a core subunit of Polycomb repressive complex2 (PRC2), undergoes proteasomal degradation. This process requires the long noncoding RNA, Hox transcript antisense intergenic RNA (HOTAIR). Intriguingly, HOTAIR interacts with PRC2 and also binds RNA‐binding E3 ligases, serving as a ubiquitination scaffold. Herein, we identified the RNA helicase, DEAD box protein 5 (DDX5), as a regulator of SUZ12 stability and PRC2‐mediated gene repression, acting by regulating RNA‐protein complexes formed with HOTAIR. Specifically, knockdown of DDX5 and/or HOTAIR enabled reexpression of PRC2‐repressed genes epithelial cell adhesion molecule (EpCAM) and pluripotency genes. Also, knockdown of DDX5 enhanced transcription from the HBV minichromosome. The helicase activity of DDX5 stabilized SUZ12‐ and PRC2‐mediated gene silencing, by displacing the RNA‐binding E3 ligase, Mex‐3 RNA‐binding family member B (Mex3b), from HOTAIR. Conversely, ectopic expression of Mex3b ubiquitinated SUZ12, displaced DDX5 from HOTAIR, and induced SUZ12 down‐regulation. In G2 phase of cells expressing the HBV X protein (HBx), SUZ12 preferentially associated with Mex3b, but not DDX5, resulting in de‐repression of PRC2 targets, including EpCAM and pluripotency genes. Significantly, liver tumors from HBx/c‐myc bitransgenic mice and chronically HBV‐infected patients exhibited a strong negative correlation between DDX5 messenger RNA levels, pluripotency gene expression, and liver tumor differentiation. Notably, chronically infected HBV patients with HCC expressing reduced DDX5 exhibited poor prognosis after tumor resection, identifying DDX5 as an important player in poor prognosis HCC. Conclusion : The RNA helicase DDX5, and E3 ligase Mex3b, are important cellular targets for the design of novel, epigenetic therapies to combat HBV infection and poor prognosis HBV‐associated liver cancer. (Hepatology 2016;64:1033‐1048)